2017
DOI: 10.1177/000313481708300212
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Dextran-40 as a Venous Thromboembolism Prophylaxis Strategy in Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy

Abstract: The incidence of venous thromboembolism (VTE) in peritoneal malignancies can approach 30 to 50 per cent without prophylaxis. Prophylaxis in cytoreductive surgeries (CRS) presents a challenge to preoperative heparin-based therapy because of an increased risk of coagulopathy and potential for bleeding. Herein, we report the large series of CRS and hyperthermic intraperitoneal chemotherapy receiving dextran-40 prophylaxis. Retrospective chart review of peritoneal malignancies patients undergoing CRS at University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Perioperative TEG hypercoagulation has also been suggested to reflect the degree of malignancy of ovarian masses (Amirkhosravi et al 2013 ). Dextran has been suggested to reduce thromboembolism in cancer surgery (Foster et al 2017 ). Dextrans have also been used in vascular surgery to diminish the risk of stroke associated with carotid endarterectomy and in “difficult” infragenicular lower extremity bypasses (Abir et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative TEG hypercoagulation has also been suggested to reflect the degree of malignancy of ovarian masses (Amirkhosravi et al 2013 ). Dextran has been suggested to reduce thromboembolism in cancer surgery (Foster et al 2017 ). Dextrans have also been used in vascular surgery to diminish the risk of stroke associated with carotid endarterectomy and in “difficult” infragenicular lower extremity bypasses (Abir et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Modified polysaccharides have shown great promise in the biomedical field. 1−8 A few nonsynthetic and semisynthetic formulations of glucans such as dextran and hydroxyethyl starch (HES) have been used clinically for the past few decades, 9,10 and their biocompatibility, biodegradability, low immunogenicity, and ability to be readily modified by various functional moieties make them attractive starting materials in the field of drug delivery. 11−19 Modification with hydrophobic moieties such as cholesterol or hydrophobic drugs allows for assembly of the polysaccharides into nanoparticles that may improve the efficacy and safety of drug delivery.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Modified polysaccharides have shown great promise in the biomedical field. A few nonsynthetic and semisynthetic formulations of glucans such as dextran and hydroxyethyl starch (HES) have been used clinically for the past few decades, , and their biocompatibility, biodegradability, low immunogenicity, and ability to be readily modified by various functional moieties make them attractive starting materials in the field of drug delivery. Modification with hydrophobic moieties such as cholesterol or hydrophobic drugs allows for assembly of the polysaccharides into nanoparticles that may improve the efficacy and safety of drug delivery. , For example, modifying HES with fatty acids allowed for assembly of HES micelles, and subsequently it was shown that propylating starch facilitates the assembly of large nanoparticles for encapsulation of doxetaxel . Using pentadecylphenol-modified dextran, Pramod et al synthesized a dual delivery nanovesicle of camptothecin and doxorubicin, which displayed synergistic improvement in anticancer activity .…”
Section: Introductionmentioning
confidence: 99%